Pemahaman Materi Operasi Bilangan Bulat Ditinjau Dari Gaya Belajar Pada Siswa Menengah - Hidriana; Gunawan Santoso; Ahmad Syamsuadi; Iswan (Jurnal Pendidikan Transformatif, 2023)
The aim of this research is to analyze the ability to understand mathematical concepts regarding integer operations in terms of the learning styles of class VII students at SMP Negeri 5 Makassar. This type of research is qualitative descriptive research. The subjects in this study were 3 students, namely 1 student with a visual learning style who got the best score on the test, 1 student with an auditory learning style who got the best score on the test, and 1 student with a kinesthetic learning style who got the best score on the test. The instruments used were learning style questionnaires, concept understanding ability tests, and interviews. The data analysis techniques in this research are data condensation, data presentation, data verification, and drawing conclusions. There are 5 indicators of concept understanding ability used in this research, namely restating a concept, classifying objects according to certain properties (according to the concept), providing examples and non-examples of the concept, presenting the concept in various forms of mathematical representation, and using , utilize, and select a particular operation or procedure. The triangulation in this research is method triangulation. Based on the research results, it shows that (1) students with a visual learning style in solving problems understanding mathematical concepts are only able to restate a concept and provide examples and not examples of the concept of integer counting operations (2) Students with an auditory learning style in solving problems understanding concepts mathematics is only able to restate a concept and provide examples and not examples of the concept (3) students with a kinesthetic learning style in solving problems understanding mathematical concepts are only able to restate a concept, and provide examples and not examples of the concept. So it can be concluded that the three subjects were only able to answer questions by fulfilling 2 of the 5 indicators of ability to understand mathematical concepts.